Survival following liver transplantation for locally advanced, unresectable intrahepatic cholangiocarcinoma. Issue 3 (27th December 2021) - McMillan, Robert R.; Javle, Milind; Kodali, Sudha; Saharia, Ashish; Mobley, Constance; Heyne, Kirk; Hobeika, Mark J.; Lunsford, Keri E.; Victor, David W.; Shetty, Akshay; McFadden, Robert S.; Abdelrahim, Maen; et al.
Abstract : Intrahepatic cholangiocarcinoma (iCCA) has previously been considered a contraindication to liver transplantation (LT). However, recent series showed favorable outcomes for LT after neoadjuvant therapy. Our center developed a protocol for neoadjuvant therapy and LT for patients with locally advanced, unresectable iCCA in 2010. Patients undergoing LT were required to demonstrate disease stability for 6 months on neoadjuvant therapy with no extrahepatic disease. During the study period, 32 patients were listed for LT and 18 patients underwent LT. For transplanted patients, the median number of iCCA tumors was 2, and the median cumulative tumor diameter was 10.4 cm. Patients receiving LT had an overall survival at 1‐, 3‐, and 5‐years of 100%, 71%, and 57%. Recurrences occurred in seven patients and were treated with systemic therapy and resection. The study population had a higher than expected proportion of patients with genetic alterations in fibroblast growth factor receptor (FGFR) and DNA damage repair pathways. These data support LT as a treatment for highly selected patients with locally advanced, unresectable iCCA. Further studies to identify criteria for LT in iCCA and factors predicting survival are warranted. Abstract : Long term survival after liver transplantation is possible for selected patients with locally‐advanced, unresectable intrahepatic cholangiocarcinoma who receive neoadjuvant therapy and demonstrate disease stability. Ivanics comments on page 685